Experimental investigation and semi-empirical modeling of snowflake melting. (1st August 2023) - Aguilar, Boris; Trontin, Pierre; Köbschall, Kilian; Dezitter, Fabien; Hussong, Jeanette; Villedieu, Philippe
Highlights: Model for the melting process of a snowflake. 2D-to-3D geometric reconstruction. Bulk-density based approach. Abstract: The melting process is studied for the case of snowflakes of aggregate type. Snowflakes are placed in the center of an acoustic levitator with a warm air flow. The evolution of the shape of the snowflake is recorded over time by a camera and the total melting time is measured. A model is proposed to describe the melting process. It is based on a simplified 3D geometric representation of the snowflake (spheroidal shape for the convex hull) and an accurate estimation of its bulk density throughout the melting process. This allows taking into account the very important change of the shape of the aggregate during the melting step and thus to be able to predict the total melting time with a much better accuracy than the existing models.